Technology for learning with arts and creativity - Patrício, Maria Raquel (2013)
The challenge posed by ageing population in the field of education and learning, the importance of new technology in the global world and solidarity between generations are factors of motivation and opportunity to contribute to a new dynamics of learning and ageing. Older people’s knowledge, wisdom and life experience will contribute through ICT for a better educational focus on values and traditions, transferring their skills and experience to the younger. This paper aims to describe the design of learning activities for the development of ICT competences among older adults within the context of informal intergenerational processes of interaction. In addition, youth learning about culture and popular wisdom is also expected, specifically in the area of arts and creativity such as local traditions in northeast Portugal (i.e. winter festivities with “caretos”, sounds and traditional songs). We intended to explore the significance of encounters and exchanges between younger and older generations for the development of interest in learning traditional arts and then use modern technology to register and preserve these memories. The outcomes will allow us to get relevant inferences to understand and develop strategies to encourage useful and significant intergenerational learning, and how both generations contribute and benefit from it. The reflections will be essential to identify new areas of teaching and learning, especially through arts and creativity supported by ICT, as well as to understand education and intergenerational learning.